Виктор Михайлович Васнецов. 1848-1926 - Барагамян А. (Великие художники, 2010)
Экземпляры: Ф4 (20220204ԁ) / Инвентарный номер: 62527 / Цена: 55.00 / Сис.шифр: 85.14 / Авт.знак: В 19 / ГРНТИ: 18.31.31 / ББК: 85.14